Water management: consumption, weed occurrence, nutrient uptake and rice yield. - Stone, Luis Fernando; Moreira, José Aloísio Alves; Filho, Austrelino Silveira (Pesquisa Agropecuaria Brasileira, 2014)
Experiments were carried out during four years in order to study the effects of water management, on its consumption, weed occurrence, nutrient uptake and rice (cv. CICA 8 and CNA- 1051 Ajuricaba) yield. The treatments were: continuous flooding during entire cicle; intermittent flooding during entire cicle; intermittent flooding during vegetative phase followed by continuous flooding during reproductive phase; subsurface irrigation by raising the water table, with rows of 0.20 m wide; subsurface irrigation, with rows of 0.30 m wide. Water consumption was high due to high percolation and lateral flow losses of 61 to 91% of total water consumption, depending on the irrigation system. Intermittent flooding used 71% less water than continuous flooding, that, however, reduced weed occurrence and increased P and Fe uptake. Subsurface irrigation increased Mn uptake. Intermittent flooding during vegetative phase followed by continuous flooding during reproductive phase produced higher rice yield due to the increasement in tillering, number of grains/panicle, and grain weight.
Keywords: irrigation; continuous flooding; intermittent flooding; subsurface irrigation; percolation; water saving; Oryza sativa.